2018
DOI: 10.1002/2017jb014491
|View full text |Cite
|
Sign up to set email alerts
|

Microseismic Monitoring of Stimulating Shale Gas Reservoir in SW China: 2. Spatial Clustering Controlled by the Preexisting Faults and Fractures

Abstract: Microseismic monitoring is crucial to improving stimulation efficiency of hydraulic fracturing treatment, as well as to mitigating potential induced seismic hazard. We applied an improved matching and locating technique to the downhole microseismic data set during one treatment stage along a horizontal well within the Weiyuan shale gas play inside Sichuan Basin in SW China, resulting in 3,052 well‐located microseismic events. We employed this expanded catalog to investigate the spatiotemporal evolution of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 43 publications
5
44
0
Order By: Relevance
“…In this study, the fast polarization directions inferred from the vertically propagating S waves are in the range of N40°–70°E, which are generally parallel to the strike directions of the natural fractures observed by microseismic monitoring studies (Chen, Meng et al, ; Meng et al, ). Such an orientation is also confirmed by well log data based on high electric conductivity (Figure b, Chen, Meng et al, ).…”
Section: Interpretation and Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…In this study, the fast polarization directions inferred from the vertically propagating S waves are in the range of N40°–70°E, which are generally parallel to the strike directions of the natural fractures observed by microseismic monitoring studies (Chen, Meng et al, ; Meng et al, ). Such an orientation is also confirmed by well log data based on high electric conductivity (Figure b, Chen, Meng et al, ).…”
Section: Interpretation and Discussionsupporting
confidence: 57%
“…In this study, the fast polarization directions inferred from the vertically propagating S waves are in the range of N40°–70°E, which are generally parallel to the strike directions of the natural fractures observed by microseismic monitoring studies (Chen, Meng et al, ; Meng et al, ). Such an orientation is also confirmed by well log data based on high electric conductivity (Figure b, Chen, Meng et al, ). On the other hand, the local maximum horizontal compressional stress is approximately aligned along the east‐west direction (Figure b, Chen, Meng et al, ), which differs significantly from the observed fast polarization direction.…”
Section: Interpretation and Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In other words, to better delineate fracture distribution, reliable locational algorithmic studies are extremely urgent. However, in many cases, we can only estimate the distance to the microseismic source from the difference between the P-and S-wave arrival times, while it is impossible to achieve the geometric shapes and original times of the events induced in a three-dimensional (3D) space (Soledad and Danilo, 2018;Chen et al, 2018) unless the direction where the energy originates from is determined using azimuth from the motion polarization analysis of both the P and S waves recorded by multistage three-component geophones (usually 12 or 16 pieces). As we focus on event location in this study, these preliminary works should already be completed.…”
Section: Microseismic Monitoring Techniquementioning
confidence: 99%